2007
DOI: 10.1159/000107673
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Selected Vitamins and Trace Elements to Immune Function

Abstract: Adequate intakes of vitamins and trace elements are required for the immune system to function efficiently. Micronutrient deficiency suppresses immune functions by affecting the innate T-cell-mediated immune response and adaptive antibody response, and leads to dysregulation of the balanced host response. This increases the susceptibility to infections, with increased morbidity and mortality. In turn, infections aggravate micronutrient deficiencies by reducing nutrient intake, increasing losses, and interferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
516
1
24

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 614 publications
(547 citation statements)
references
References 262 publications
6
516
1
24
Order By: Relevance
“…6 Whereas, another randomized controlled trial that supplemented elderly participants with zinc reported no change in immune response to influenza vaccine in spite of restoration of circulating zinc levels. 7 While copper is known to have a positive effect on immune response, 4 this study found a positive relationship between immune response to influenza vaccine and copper level only when being overweight was included in the model. Day 0 magnesium and phosphorus levels were also significantly related to immune response to A/H1N1 levels when being overweight was included in the model.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…6 Whereas, another randomized controlled trial that supplemented elderly participants with zinc reported no change in immune response to influenza vaccine in spite of restoration of circulating zinc levels. 7 While copper is known to have a positive effect on immune response, 4 this study found a positive relationship between immune response to influenza vaccine and copper level only when being overweight was included in the model. Day 0 magnesium and phosphorus levels were also significantly related to immune response to A/H1N1 levels when being overweight was included in the model.…”
Section: Discussionmentioning
confidence: 52%
“…This study did not find positive relationships between immune response to influenza vaccine and zinc, a mineral commonly found to be related to immune function. [3][4][5] A randomized controlled trial of elderly adults supplemented with vitamins, minerals, vitamins and minerals, or neither found that the minerals only-and vitamins plus minerals-supplemented groups had higher antibody response to influenza vaccination, although there was no difference among groups on number of individuals with respiratory infections. 6 Whereas, another randomized controlled trial that supplemented elderly participants with zinc reported no change in immune response to influenza vaccine in spite of restoration of circulating zinc levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VA deficiency impairs both innate immunity and adaptive immune response to infection, resulting in impaired ability to counteract extracellular pathogens [24]. The present study indicated that the immune condition of JB cattle during the feeding stage is compromised by following VA deficiency.…”
mentioning
confidence: 54%